2011
DOI: 10.1037/a0024480
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of parenting stress among gay adoptive fathers in the United States.

Abstract: The authors examined correlates of parenting stress among 230 gay adoptive fathers across the United States through an Internet survey. As with previous research on adoptive parents, results showed that fathers with less social support, older children, and children who were adopted at older ages reported more parenting stress. Moreover, gay fathers who had a less positive gay identity also reported more parenting stress. These 4 variables accounted for 33% of the variance in parenting stress; effect sizes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
1
9

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(86 citation statements)
references
References 40 publications
9
67
1
9
Order By: Relevance
“…Thus, these problems would not be generated by parents or caregivers, but by peers and, in a general sense, by society. As acknowledged by Cameron & Cameron (2002), Tasker & Patterson (2007) or Tornello et al (2011), children raised in gay and lesbian families may experience more difficulties during childhood, simply due to growing up in a family that departs somewhat from behaviour socially considered to be "normal", rather than due to the sexual orientation of their fathers or mothers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these problems would not be generated by parents or caregivers, but by peers and, in a general sense, by society. As acknowledged by Cameron & Cameron (2002), Tasker & Patterson (2007) or Tornello et al (2011), children raised in gay and lesbian families may experience more difficulties during childhood, simply due to growing up in a family that departs somewhat from behaviour socially considered to be "normal", rather than due to the sexual orientation of their fathers or mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus begins a complex multistage process in which a variety of professionals (psychologists, lawyers and social workers) play a role within a multi-disciplinary team. Thus, the implicit beliefs of the professionals working with these children affect the entire adoption process, since they face the daily challenge of deciding whether a couple is suitable to adopt, and assessing whether an adoption is a success (Barranco, 2011;Gergen, 2006;Hartman, 1979;Palacios & Amorós, 2006;Paul & Arruabarrena, 1996;Ryan & Mallon, 2011;Shadish et al, 1991;Tornello et al, 2011). Therefore, social professionals should regularly review their personal attitudes toward gay men and lesbian women as parents, in the light of scientific studies that show that GLBT people can become good parents (Gonzalez et al, 2004;Ryan & Mallon, 2011;Tasker & Patterson, 2007;Turner et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Many gay fathers became fathers in the context of a heterosexual relationship, although increasingly, gay male couples are adopting children, partnering with lesbian mothers, or using surrogate carriers to father children. 95,96 Children with gay parents are comparable to children with heterosexual parents on key psychosocial developmental outcomes. [97][98][99] Large sample surveys from the 2003-2013 American Time Use Survey (N = 44 188) showed that women with same-sex partners as well as opposite-sex partners and men with same-sex partners spent more time with their children than did men with opposite-sex partners.…”
Section: Improved Understanding Of Other Groups Of Fathersmentioning
confidence: 99%
“…In their comparison of the psychological well-being of preschool children adopted in infancy by matched groups of lesbian, gay, and heterosexual couples, Farr et al (2010) and Tornello et al (2010) found that children adopted by same-sex couples were as well-adjusted as those adopted by heterosexual couples, according to both parents' and teachers' reports on the CBCL. Irrespective of family structure, the authors concluded that the factors related to child adjustment were positive parenting, the absence of parenting stress, and harmonious couple relationships.…”
Section: Psychological Adjustment Of Young Childrenmentioning
confidence: 99%
“…Where differences were found, these reflected more positive parental well-being and parent-child relationships in gay, rather than heterosexual, families. In a study of adoptive two-parent families in the United States, few differences between gay, lesbian, and heterosexual families were found in parenting stress, parental discipline, or parental relationship satisfaction (Farr, Forssell, & Patterson, 2010;Tornello, Farr, & Patterson, 2010). Erich, Leung, and Kindle (2005) collected data from a convenience sample of lesbian and gay adoptive parents of children of varying ages.…”
Section: Parentingmentioning
confidence: 99%